Improving the Performance of Web Developers at PT Terakorp Indonesia Through Work Motivation, Compensation, and Work-Life Balance - Biwan Radita; Asti Nur Aryanti; Gurawan Dayona (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2026)
The performance of web developers plays a crucial role in supporting the success of technology companies, as it is closely related to productivity, system development quality, and the ability to adapt to evolving business demands. This study aims to examine the effects of compensation and work-life balance on work motivation and employee performance, as well as to evaluate the role of work motivation as a mediating variable. The research was conducted at PT Terakorp Indonesia, involving 162 web developers selected using a saturated sampling technique. This study employs a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) as the analytical method. The findings reveal that compensation and work-life balance have positive effects on both work motivation and employee performance. Furthermore, work motivation is confirmed to have a positive impact on improving employee performance. Indirectly, work motivation successfully mediates the relationship between compensation and work-life balance with employee performance. These results highlight the importance of managing both financial and non-financial factors to enhance web developer performance through continuous and sustainable strategies in today’s digital organizations.